Efek Kombinasi Vermikompos dan Mikrobia Terhadap Pertumbuhan dan Hasil Tanaman Kangkung (Ipomea Reptans P.) Yang Ditanam Pada Residu Media Tanam Hidroganik - Ayis Dwi Dharmayanto; Anis Rosyidah; Nurhidayati Nurhidayati (AGRONISMA, 2021)
This study aims to test the effects of various microbial concentrations and vermicompost doses on the growth and yield of water spinach grown on the residue of hydroganic growing media. This research was a pot experiment conducted in a plastic house using a factorial randomized design consisting of 2 factors. The first factor consisted of three levels of concentration of microbial solutions, namely without microbes, 25 ml/ liter of water, and 50 ml/liter of water. The second factor consisted of four levels of vermicompost doses, namely without vermicompost, 150 g/pot, 300 g/pot, 450 g/pot. All treatment combinations were repeated 3 times and each replication used 4 plant samples. The variables observed were growth and yield variables. The collected data were analyzed using the F-test with a significant level of 5%. If it showed a significant effect followed by the Tukey-test with a level of 5%. The results showed that the interaction of the combination treatment of microbial concentration and vermicompost dose had a significant effect on the growth and yield of water spinachÂ  at the age of 29 DAP. The best yields were found in the treatment of microbial concentrations of 25 ml /liter of water and 300 g/pot of vermicompost with an average yield of fresh weight per plant, fresh weight per pot, dry weight per plant, and dry weight per pot ofÂ  20.11 g, 129.92 g ,1.70 g, 1.70 g, and 11.02 g respectively. These results were not significantly different from the treatment of microbial concentrations of 25 ml/ liter of water and 450 g vermicompost / pot with an average yield of fresh weight per plant, fresh weight per pot, dry weight per plant, and dry weight per pot of 23.36 g, 139.00 g, 2.18 g, and 12.93 g respectively. The results suggest that the residual of hydroganic media can be reused for planting by adding a microbial solution of 25 ml/liter of water and vermicompost at a dose of 300-450 g/pot.